Music Therapy for Chronically ill Patient - Putriana, Maria Magdalena Greda; Soetjipto; Hendy Muagiri Margono; Budi Kristiano (Jurnal Psikiatri Surabaya, 2022)
Chornic illness puts a person at increased risk for developing anxiety or an anxiety disorder. Most often, chronic diseases are incurable, and treatment is focused primarily on the management of symptoms. Patients with chronic diseases commonly report fears of illness or symptoms recurring or worsening. The more this illness may consume a person's life and thoughts, the more negativity tends to take over. Music can affect a person at psychological or emotional aspect during treatment of an illness or injury.